Edge sharpening for diabetic retinopathy detection - Yazid, H.; Arof, Hamzah; Mokhtar, Norrima (2010)
People with diabetes may face eye problem as a complication of diabetes. These eye problems can cause vision loss and even blindness. There are several lesions that appear such microaneurysms, hemorrhages, cotton wool spots and exudates. Exudates tend to form ring, around area of diseased vessel and appeared as yellowish-white deposits with well-defined edges meanwhile cotton wool spots are grayish-white with poorly defined fluffy edges. Exudates can be highlighted from the background easier rather than cotton wool spots since it has well defined edge. In order to detect these lesions, a proper technique is needed to segment the cotton wool spots and exudates from the background. Therefore, this paper is proposed to sharpen the edge to simplify the segmentation process for cotton wool spots and exudates through ramp width reduction.